Intention to adopt personal cloud storage services: The case of university students - Mohamad, Noorman Masrek; Mohamed Jalaldeen, Mohamed Razi (2016)
Studies on personal cloud storage services (PCSS) adoption in the context of Malaysia is still very limited. Against this concern, a study was undertaken with the aim of investigating factors that could influence mobile learning adopting. Drawing upon The Unified Theory of Acceptance and Use of Technology (UTAUT) and two other variables which are perceived credibility and personal innovativeness, an empirical based framework was developed to identify predictors of PCSS. Employing a survey research method involving 267 respondents from Universiti Teknologi MARA, the results showed that performance expectancy, effort expectancy, social factors, facilitating conditions, perceived credibility and personal innovativeness are strong determinants of intention to adopt PCSS. The present study provides both a theoretical and practical contributions to understanding the predictors of intention to adopt PCSS and should be of interest to both researchers and practitioners.